2008
DOI: 10.1002/cncr.23187
|View full text |Cite
|
Sign up to set email alerts
|

Predicting response and resistance to endocrine therapy

Abstract: Selection for endocrine therapy requires the identification of markers that accurately predict response/resistance. In this report, the authors review their pub-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
17
0
2
Order By: Relevance
“…The most consistently differentially expressed genes (with the lowest predicted FDRs) were seen for pre-versus post-treatment matched responding samples, supporting the rationale for identifying consistent changes in individuals. Analysis of neoadjuvant letrozole treatment in a previous study also suggested responding tumours have similar, more consistent gene expression profiles, whilst nonresponding (resistant) tumours have multiple patterns of gene changes [24,47].…”
Section: Discussionmentioning
confidence: 91%
“…The most consistently differentially expressed genes (with the lowest predicted FDRs) were seen for pre-versus post-treatment matched responding samples, supporting the rationale for identifying consistent changes in individuals. Analysis of neoadjuvant letrozole treatment in a previous study also suggested responding tumours have similar, more consistent gene expression profiles, whilst nonresponding (resistant) tumours have multiple patterns of gene changes [24,47].…”
Section: Discussionmentioning
confidence: 91%
“…These have confirmed that aromatase inhibitor treatment is associated with changes in expression of genes classically associated with oestrogen regulation such as KIAA0101, ZWINT, TFF1 and IRS1, and cell cycle progression most notably mitotic phase proteins such as CDC2, CCNB1 and CKS2. Although more frequent in clinically responding tumours, these changes also occur in clinically non-responsive tumours [24,25]. As a consequence, they are unlikely to be reliable predictors of clinical response.…”
Section: Molecular Responsementioning
confidence: 91%
“…There have been recent key publications [21][22][23][24][25]. For example, early changes in gene expression have been identified by comparing microarray analyses from paired tumour core biopsies taken before and after 14 days' neoadjuvant treatment with letrozole [21][22][23].…”
Section: Molecular Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Gene expressions were measured by microarray in biopsies of breast cancer taken before treatment, after 2 weeks of neo-adjuvant letrozole and at surgery (after 3+ month of letrozole). Full data available in Miller et al [25] Changes in proliferative and classic oestrogen-responsive genes had no strong association with clinical response-although more frequent in clinically responding tumours, fall of these genes could be detected in both clinical responders and non-responders [48,144]. More recent interrogation of a similar dataset of letrozole-treated tumours has generated a 4-gene predictive index, which was validated on an independent neo-adjuvant anastrazole dataset [145].…”
Section: Signatures To Predict Neo-adjuvant Response To Aismentioning
confidence: 95%